Estrutura e composição de uma vegetação ripária, relações dendrocronológicas e climáticas na Serra dos Macacos em Tobias Barreto, Sergipe-Brasil - Nogueira Júnior, Francisco de Carvalho (2011)
This work was done in the caatinga dominium in an area of 220 hectares of forest located in the Serra dos Macacos Canyon, municipality of Tobias Barreto, in the period 2009 to 2010. The aim was to diagnose the structure, composition and coverage of vegetation for conservation purposes and conduct a survey dendrochrological trees species. We sampled about 12000 m2 of forest, divided into three plots of 4000 m2 in order to determine the phytosociological parameters of the community tree-shrub canopy and herbaceous understory, species richness and dendrochronological survey of tree species forming rings growth. The plots were distributed in a transect of 1500 m with reference to the creek bed at the Burrow Monkeys at altitudes of 360, 420 and 500 meters to sea level. The trees of the Canyon have two defined strata of canopy and understory shrub and vegetation type with the formation of riparian vegetation, which closed canopies and structured with individuals up to 25 m high and trunk circumference (CAP) of up to 160 cm. The herbaceous layer in the understory has a rich diversity of bromeliads (8) species recorded in the Atlantic. The richness of the floristic composition of 93 species were identified. The vertical structure of vegetation in relation to height, CAP showed strong adjustment of the curves of distribution and abundance "J" reversed indicating that the community is present in mature or stable stage of regeneration. The phytosociological study determined the dominance of the family Fabaceae (Leguminosae - Caesalpinioideae, Faboideae and Mimosoideaee) comprising 17 species of caatinga. The structural patterns of the populations assessed by the Index of Importance Value Index Phytosociology and tree cover in the community of Canyon had a distance-dependent spatial distribution of stream and associated with the behavior of canopy opening, reinforced the idea of riparian vegetation with semideciduous. The analysis of tree cover and shrubs using the GLA (Gap Light Analyzer) demonstrated that semidecidual ranged 30-70% open canopy in the dry season or month in February and a canopy closure of 80 to 90% in September, post-rain season. Prospecting dendrochronological community found that 10 species in the Serra dos Macacos have potential in the formation of growth layers. The analysis of a population of 86 individuals Pseudobombax marginatum (Malvaceae), with the objective of determining the age of the trees through the rings of growth through cross-dating series, we obtained a chronology of 83 sets of growth rings 51 individuals (2353 rings P. marginatum), yielding a value of inter-correlation of 0.449, with mean sensitivity of 0.522, while the number of missing rings was less than 3.0%. The principal component analysis (PCA) indicated that the first components explained 64.58% by 61.23% and ARSTAN chronology Residual variance (ANOVA) of plant growth by estimating the chronological age of the trees up to 62 years in the community. The formation of the rings of annual growth is positively correlated with precipitation for the current year (between April and July) with the temperature of the previous year (September to November) and is associated with deciduous species showed that in the dry season. The behavior of tree growth of revealed significant variations in the rate of average annual increment of 2.15 mm / year, and the population mean age was 27 years. The analysis of climatic parameters was established through a series of 96 years (1914-2010) for precipitation and temperature series of about 50 years (1967-2007) obtained from the Meteorological Station of Samambaia, located at 9 km near of the Canyon. Temperature data were calibrated with data obtained from the SST NOAA (National Oceanic and Atmospheric Administration). Temperature data location had a temperature range above 9ºC, different from the 6ºC as described for the NEB (Northeast of Brazil) and showed marked seasonal climate with increased precipitation and lower temperatures during the months from March to July and rainfall lower and higher temperatures between September and February. The climate for the region of Tobias Barreto proved to be mainly influenced by anomalies in sea SST (surface temperatures). This study establishes for the first time a model for predicting age of tree species associated with the climate in the Northeast of Brazil. Species richness and occurrence of rare species in this enclave in the caatinga forest contributes significantly to the goals of preservation and conservation of this biome.